2020
DOI: 10.1371/journal.pone.0240330
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hfq and sigE on the tolerance of Zymomonas mobilis ZM4 to furfural and acetic acid stresses

Abstract: Zymomonas mobilis, as an ethanologenic microorganism with many desirable industrial features, faces crucial obstacles in the lignocellulosic ethanol production process. A significant hindrance occurs during the pretreatment procedure that not only produces fermentable sugars but also releases severe toxic compounds. As diverse parts of regulation networks are involved in different aspects of complicated tolerance to inhibitors, we developed ZM4hfq and ZM4-sigE strains, in which hfq and sigE genes were overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…As shown in Figure 1D, all glucose was consumed by ZM4-hfq to achieve a maximum ethanol titer of 25.82 g/L within 24 h, almost 6 h faster than that of control, while 6.83 g/L residual glucose was still detected at 36 h by strain ZM4-Δhfq. All these results indicated that hfq in Frontiers in Bioengineering and Biotechnology frontiersin.org Z. mobilis contributes to the ethanol tolerance, just as its positive roles responding to other stresses such as furfural and acetic acid (Yang et al, 2010;Nouri et al, 2020).…”
Section: Hfq Overexpression Enhanced Ethanol Tolerance In Z Mobilismentioning
confidence: 90%
“…As shown in Figure 1D, all glucose was consumed by ZM4-hfq to achieve a maximum ethanol titer of 25.82 g/L within 24 h, almost 6 h faster than that of control, while 6.83 g/L residual glucose was still detected at 36 h by strain ZM4-Δhfq. All these results indicated that hfq in Frontiers in Bioengineering and Biotechnology frontiersin.org Z. mobilis contributes to the ethanol tolerance, just as its positive roles responding to other stresses such as furfural and acetic acid (Yang et al, 2010;Nouri et al, 2020).…”
Section: Hfq Overexpression Enhanced Ethanol Tolerance In Z Mobilismentioning
confidence: 90%
“…Recent efforts in Z. mobilis engineering have also enabled several strains to tolerate furfural and acetic acids, which are the predominant toxic inhibitors during lignocellulosic ethanol production [ 92 , 93 ]. Nouri et al [ 94 ] developed recombinant strains with improved tolerance against the multiple inhibitors by overexpressing the genes hfq (a transcription regulator) and sigE (a transcription factor). Furthermore, strain engineered to express sigE also showed 2-fold and 4-fold higher ethanol yields than the hfq-overexpressing strain and parental strain, respectively.…”
Section: Recent Metabolic Advances In Microorganism For Biofuel Produ...mentioning
confidence: 99%
“…(2) the genes related to macromolecule synthesis are upregulated to resist furfural stress (Miller et al, 2009;Yang et al, 2020); and (3) transcription factors regulate the expression of multiple genes in response to stress (He et al, 2012;Nouri et al, 2020). However, the defined roles of these corresponding genes are not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Under furfural stress, the growth and survival of Z. mobilis were inhibited, and the specific production rate of ethanol was correspondingly reduced ( Franden et al, 2009 ; Nouri et al, 2020 ). In addition, furfural also inhibits the synthesis of various proteins, causes DNA damage, and leads to the differential expression of genes involved in membrane and cell wall biogenesis, transcriptional regulators, and energy metabolism ( He et al, 2012 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation